Design and Implementation of A Hot Sealing System on A Bag Machine Based on PLC - Tauhid Tauhid; Nana Sutarna; Handri Santoso (Eduvest - Journal of Universal Studies, 2025)
The adhesive or sealing system using the type of bag sealing machine used in the packaging industry is generally using a full-automatic continuous hot sealing machine which is the result of the development of a manual hot sealing type that uses a type of tape sealing bag (duct tape) such as the one in PT.X. Sealing bag problems that often occur are unstable heating processes, clamping settings and also cooling systems that are too fast. Planning the appropriate machine system and program control system can eliminate the problems caused by the sealing in several ways, including; Conducting system simulations and program design based on observation data, assembling and testing the built system. Conducting trials and tests of machine performance as well as testing the results of the bag sealing process. Furthermore, an evaluation of system performance and sealing bag quality results was carried out as well as improvements in system performance results in accordance with ASMEF88 standards. The design and implementation of the manufacture of automation machines and monitoring systems will involve PLC components and IoT technology. So that during the process, the system can be monitored in real time. The final result of this study is expected to reduce the problem of broken sealing in packaging bags by 1%.